Exploring academic stress and coping strategies among first-semester students in an ELT master’s program - Aulia Asma Rabbani; Nunung Suryati (Tell : Teaching of English Language and Literature Journal, 2026)
Academic stress is a common challenge for master’s students, especially in their first semester. This study examines academic stress levels and coping strategies among first-semester students in an ELT master’s degree program in Malang, Indonesia, using an explanatory mixed-method design. Quantitative data were collected beginning by employing the Educational Stress Scale for University Students (ESSA) and the BRIEF-COPE questionnaire in order to gain information about the stress level and the most frequently employed coping strategies. Based on these findings, further qualitative data collection involved semi-structured interviews to explore how these situations shaped students' experiences and behaviors in academic life. Guided by the Transactional Model of Stress and Coping (Lazarus & Folkman, 1984), the results show that 60% of participants experienced high academic stress, mainly related to heavy academic load, time pressure, academic English demands, and limited familiarity with research tasks. In coping with these pressures, it appears that students tended to rely initially on emotion-focused or avoidant coping, gradually shifting toward more problem-focused approaches, particularly planning and active coping. These findings suggest the need for early academic support, including mentoring, language-sensitive instruction, and structured guidance to support students’ transition into postgraduate study.